2017
DOI: 10.12659/msm.902956
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and Single Nucleotide Polymorphisms in the Insulin-Like Growth Factor 1 Promoter with Insulin Sensitivity and Insulin Secretion

Abstract: BackgroundTo investigate associations of the CA microsatellite and rs35767, rs5742612, and rs2288377 polymorphisms and the single nucleotide polymorphism (SNP) haplotypes with and without the CA microsatellite in the IGF1 promoter with insulin sensitivity and secretion.Material/MethodsThe CA microsatellite and SNPs were genotyped in 389 type 2 diabetes mellitus (T2DM) patients. A 75 g oral glucose tolerance test (OGTT) was given to all the participants. Associations of the genotypes and haplotypes with insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…37 In addition, it was found that IGF-1 may induce lymphangiogenesis and facilitates lymphatic metastasis, 38 and be associated with larger tumor size, local LNM, and worse prognosis in cancers. Wang et al 41 reported that the G allele of rs5742612 was found to be associated with decreased insulin sensitivity and increased insulin secretion. In this study, we found that IGF1 rs5742612 A > G polymorphism might increase the risk of LNM among patients with EGJA.…”
Section: Discussionmentioning
confidence: 99%
“…37 In addition, it was found that IGF-1 may induce lymphangiogenesis and facilitates lymphatic metastasis, 38 and be associated with larger tumor size, local LNM, and worse prognosis in cancers. Wang et al 41 reported that the G allele of rs5742612 was found to be associated with decreased insulin sensitivity and increased insulin secretion. In this study, we found that IGF1 rs5742612 A > G polymorphism might increase the risk of LNM among patients with EGJA.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, acid-base homeostasis may in uence calcium and magnesium absorption in the kidney [56] and consequences of serum calcium and magnesium were related to insulin sensitivity [57,58]. Finally, yet importantly, metabolic acidosis may reduce the secretion of IGF-I [59] and inhibit insulin sensitivity [60]. On the other hand, this nding was incongruent with a longitudinal study involved 911 older non-diabetic community-dwelling Swedish men [33].…”
Section: Discussionmentioning
confidence: 97%
“…Thirdly, acid–base homeostasis may influence calcium and magnesium absorption in the kidney [ 70 ] and consequences of serum calcium and magnesium are related to insulin sensitivity [ 71 , 72 ]. Finally, yet importantly, metabolic acidosis may reduce the secretion of IGF-I [ 73 ] and inhibit insulin sensitivity [ 74 ]. On the other hand, this finding was incongruent with a longitudinal study involving 911 older non-diabetic community-dwelling Swedish men [ 34 ].…”
Section: Discussionmentioning
confidence: 99%